Parent perspectives about pediatric urology telemedicine visits before and after COVID-19-driven rapid implementation - Walton, Ryan F.; Arora, Hans C.; Berkowitz, Rachel J.; Rosoklija, Ilina; Cheng, Earl Y.; Johnson, Emilie K. (Frontiers in Urology, 2022)
Research Objective: Telemedicine is now a critical healthcare delivery modality. Prior studies of telemedicine in pediatric urology are lacking parent/patient perspectives. This study aims to assess interest in and factors associated with willingness to participate in telemedicine, and to compare perceptions of telemedicine before and after pandemic-related implementation. Study Design: This was a cross-sectional study of parents of pediatric urology patients that attended in-person clinic visits (Pre-Telemedicine cohort; January-March 2020) and telemedicine visits (Post-Telemedicine cohort; April-July 2020). Principal Findings: The response rates were 83.4% (Pre-Telemedicine, N=205) and 32.5% (Post-Telemedicine, N=89). Overall, most parents had a college or graduate level degree (71.9%), private insurance (71.6%), and a plurality were 36-40 years old (30.7%). Their children were mostly white (68.9%), 23.7% were Hispanic/Latino, and the median patient age was 3.3 years (range: 0.1–32.1). There were no demographic differences between the Pre- and Post-Telemedicine sub-groups. Pre-Telemedicine Most (84.3%) were willing to participate in a new, follow-up, or post-operative telemedicine visit. There were no associations between demographics and willingness. Comfort in video visits without a physical exam (3.23% Unwilling vs 38.2% Willing, =<0.001), comfort with technology (22.6% vs 71.6%, p=<0.001), belief that quality of care is similar between telemedicine and in-person visits (3.23% vs 24.0%, p=<0.001), and estimated costs from in-person visits (6.67% vs 30.3%, p=0.004) were all positively associated with willingness. Post-Telemedicine Most indicated that telemedicine met their needs (88.6%), and that they were satisfied with the both the quality of technology used (83%) and the interaction with the urologist (89.9%) during the telemedicine visit. Comparison of Pre-and-Post-Telemedicine In reference to the Pre-Telemedicine respondents, Post-Telemedicine respondents more frequently strongly agreed that telemedicine is as private (51.5% vs 77.5%, p=<0.001), secure (49.5% vs 66.3%, p=0.02), and complete (33.2% vs 51.1%, p=0.02) as in-person visits. Conclusions: Most parents had high willingness to participate and positive perceptions of telemedicine prior to the COVID-19 era. Factors associated with willingness were elucidated. Families that participated in telemedicine reduced direct costs and saved time. Lastly, these results suggest that confidence in telemedicine had increased after experience with telemedicine. These data support continued telemedicine access and coverage/reimbursement beyond the pandemic.